Experiences of professional nurses regarding shortage of resources at a tertiary hospital in Gauteng Province, South Africa: qualitative study - Makoasha Philistus Jiyane; Sisinyana Hannah Khunou (Jurnal Ners, 2023)
Background: Shortage of resources in hospitals is a global problem with South Africa not being excluded. These leads to a situation where most health care workers especially professional nurses (PNs)  leave the health institutions to private hospitals or abroad for better opportunities. The study explored and described professional nurses’ experiences regarding shortage of resources at a tertiary hospital in Gauteng Province.